Dampak Perubahan Cuaca dan Kemampuan Adaptasi Petani Terhadap Produksi Tanaman Hortikultura di Kabupaten Timor Tengah Utara - Funan, Anselma Ose; Sipayung, Boanerges Putra; Nubatonis, Agustinus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyze the impact of weather changes and the adaptive capacity of horticultural crop farmers in North Central Timor District. The methods used in this study were cobb-douglass analysis and multinomial logistic regression. The number of samples in this study amounted to 150 respondents. The results showed that the production of horticultural crops in North Central Timor District increased by 40.6%. Horticultural farmers in North Central Timor District are at a moderate stage of adapting to weather changes. Where the majority of farmers who are adapting as many as 61 people, unable to adapt 30 and have adapted 59 people. The adaptability of farmers is influenced by the independence variable. In this case farmers manage farms with their own capital ownership, besides that farmers also try to find solutions to problems regarding farms that are managed.